Morphology and energy transfer study between conjugated polymers thin films: experimental and theoretical approaches. (24th May 2022) - Wouk, Luana; Holakoei, Soheila; Benatto, Leandro; Pacheco, Kaike Rosivan Maia; de Jesus Bassi, Maiara; de Oliveira, Camilla K B Q M; Bagnis, Diego; Rocco, Maria Luiza Miranda; Roman, Lucimara Stolz
Abstract: In this paper, the effect of a silafluorene derivative copolymer, the poly[2, 7-(9, 9-dioctyl-dibenzosilole)-alt-4, 7-bis(thiophene-2-yl)benzo-2, 1, 3-thiadiazole] (PSiF-DBT) sensitized by a simpler homopolymer, the poly[2-methoxy-5-(3′, 7′-dimethyloctyloxy)-1, 4-phenylenevinylene] (MDMO-PPV) were investigated in a bilayer and ternary blend configuration. The energy transfer between the polymers prior to electron transfer to the acceptors can be an efficient alternative to photocurrent improvement in photovoltaic devices. The interactions between the two donor polymer films were evaluated optically and morphologically with several experimental techniques and correlated to the photovoltaic performance. Improved photon to charge conversion was observed in the blend films at different device geometries—considering bilayer devices with fullerene and inverted flexible devices blade coated in air conditions with a non-fullerene small molecule acceptor. Resonant Auger spectroscopy using the core–hole clock method was employed to evaluate the ultrafast charge delocalization times of conjugated polymers in the low-femtosecond regime. Density functional theory and time-dependent DFT methods were used to help understand some experimental observations. The results show that the homopolymer can improve the absorption spectra and the nonradiative-energy transfer from MDMO-PPV to PSiF-DBT and act as a photosensitizer in the copolymer units. In addition, the PSiF-DBT blended with MDMO-PPV exhibits a more organized structure than the neat material resulting in better absorption stability of films kept under continuous illumination.